Cover Image. (13th March 2019) - Piccin, Andrea; Murphy, Ciaran; Eakins, Elva; Rondinelli, Maria Beatrice; Daves, Massimo; Vecchiato, Cinzia; Wolf, Dominik; Mc Mahon, Corrina; Smith, Owen P.
Abstract : The cover image is based on the Review Article INSIGHT INTO THE COMPLEX PATHOPHYSIOLOGY OF SICKLE CELL ANAEMIA AND POSSIBLE TREATMENT by Andrea Piccin et al., https://doi.org/10.1111/ejh.13212 .